Recommendations for Management of Equine Athletes with Cardiovascular Abnormalities. (14th March 2014) - Reef, V.B.; Bonagura, J.; Buhl, R.; McGurrin, M.K.J.; Schwarzwald, C.C.; van, G.; Young, L.E.
<x xml:space="preserve">Abstract</x> Murmurs and arrhythmias are commonly detected in equine athletes. Assessing the relevance of these cardiovascular abnormalities in the performance horse can be challenging. Determining the impact of a cardiovascular disorder on performance, life expectancy, horse and rider or driver safety relative to the owner's future expectations is paramount. A comprehensive assessment of the cardiovascular abnormality detected is essential to determine its severity and achieve these aims. This consensus statement presents a general approach to the assessment of cardiovascular abnormalities, followed by a discussion of the common murmurs and arrhythmias. The description, diagnosis, evaluation, and prognosis are considered for each cardiovascular abnormality. The recommendations presented herein are based on available literature and a consensus of the panelists. While the majority of horses with cardiovascular abnormalities have a useful performance life, periodic reexaminations are indicated for those with clinically relevant cardiovascular disease. Horses with pulmonary hypertension, CHF, or complex ventricular arrhythmias should not be ridden or driven.